PENINGKATAN HASIL BELAJAR PENYAJIAN DATA MENGGUNAKAN MODEL PROJECT BASED LEARNING DI KELAS IV SD NEGERI 13 PASAR REMAJA KOTA SAWAHLUNTO - Riska Wijaya, Diva; Andika, Refiona; Zainil, Melva; Ningsih, Yarisda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted because the learning outcomes of fourth- grade students at SD Negeri 13 Pasar Remaja, Sawahlunto City, on data presentation are still relatively low. This low learning outcome is indicated by a class average score of 68.36, with a learning completion percentage of only 45.45%. Consequently, some students have not yet achieved the Learning Objective Achievement Criteria (KKTP). This condition is influenced by the teacher-centered learning process, students' lack of active participation in discussions and collaboration, and their inability to construct knowledge independently. Therefore, this study aims to describe the improvement in student learning outcomes through the application of the Project-Based Learning model to data presentation in fourth-grade students at SD Negeri 13 Pasar Remaja, Sawahlunto City. This study is a Classroom Action Research (CAR) with qualitative and quantitative approaches, implemented in two cycles. Each cycle consists of planning, action, observation, and reflection. The research subjects were teachers and 22 fourth-grade students at SD Negeri 13 Pasar Remaja, Sawahlunto City, in the 2025/2026 academic year. Data were obtained through an in-depth learning plan (RPM) assessment, observations of teacher and student activities, and learning outcome tests. Data were analyzed using qualitative and quantitative data analysis techniques. The results showed that the implementation of the Project-Based Learning model improved the quality of the learning process and student learning outcomes. The percentage of student activity increased from 75% in Cycle I to 96.4% in Cycle II, qualifying as very good. Furthermore, the average learning outcome score increased from 68.36 at the initial level to 74.54 in Cycle I, then again to 85 in Cycle II. The learning completion percentage also increased from 45.45% at the initial level to 72.73% in Cycle I and reached 95.45% in Cycle II. Thus, it can be concluded that the implementation of the Project-Based Learning model can improve the quality of the learning process and students' mathematics learning outcomes in data presentation material in fourth grade at SD Negeri 13 Pasar Remaja, Sawahlunto City.